Strategic treatments with systemic biocides to control Rhipicephalus (Boophilus) microplus (Acari: Ixodidae) in northwestern Argentina = Tratamientos estratégicos con biocidas sistémicos para el control de Rhipicephalus (Boophilus) microplus (Acari: Ixodidae) en el noroeste de Argentina - Nava, Santiago; Mangold, Atilio Jose; Canevari, Jose Tobias; Morel, Nicolas; Guglielmone, Alberto (Facultad de Ciencias Veterinarias, Universidad de Buenos Aires, 2019)
This work was performed to evaluate two different schemes of treatment with systemic biocides to control Rhipicephalus microplus in northwestern Argentina. Treatments were applied from late winter to late spring to act on the small 1st spring generation of R. microplus, precluding the rise of the larger generations of autumn. In the scheme 1, calves were treated with fluazuron on days 0 and 49, and with fipronil on day 105. In the scheme 2, calves were treated with ivermectin 3.15%, fluazuron and fipronil on days 0, 28 and 83, respectively. The number of ticks observed on control group was significantly higher than the number of ticks in the treated groups. The percentage reduction in numbers of ticks with the control scheme 1 was more than 90% during practically all study period. The treatment applied in the scheme 2 provided values of reduction higher than 90% in September, October, December, January and February, but not in November (87.49%) and March (88.78%). The results showed that both treatments schemes achieved an acceptable control level, but complementary studies are needed to determine if the R. microplus ticks detected in early autumn could increase in time to high levels.